2017
DOI: 10.1038/s41598-017-02666-4
|View full text |Cite
|
Sign up to set email alerts
|

Potent anti-cancer effects of less polar Curcumin analogues on gastric adenocarcinoma and esophageal squamous cell carcinoma cells

Abstract: Curcumin and its chalcone derivatives inhibit the growth of human cancer cells. It is reported that replacement of two OH groups in curcumin with less polar groups like methoxy increases its anti-proliferative activity. In this study, we explored benzylidine cyclohexanone derivatives with non-polar groups, to see if they possess increased anti-cancer activity. Novel 2,6-bis benzylidine cyclohexanone analogues of curcumin were synthesized, and their inhibitory effects on gastric adenocarcinoma (AGS) and esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Curcumin is limited by its hydrophobic nature, poor water solubility, low bioavailability, and chemical instability. New advances in pharmaceutical strategies, such as nanoencapsulation, may overcome these limitations [1, 18, 21, 23]. Additionally, the isolation of curcumin from the other constituents in turmeric may reduce its therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is limited by its hydrophobic nature, poor water solubility, low bioavailability, and chemical instability. New advances in pharmaceutical strategies, such as nanoencapsulation, may overcome these limitations [1, 18, 21, 23]. Additionally, the isolation of curcumin from the other constituents in turmeric may reduce its therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the isolation of curcumin from the other constituents in turmeric may reduce its therapeutic potential. Curcumin’s demonstrated therapeutic benefit and increased bioavailability when used as an adjunct drug in therapy supports this argument [1, 4, 18, 21, 23, 33]. A future trial exploring turmeric or a combined nutraceutical therapy for radiation dermatitis may yield positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the inhibitory effects of new 2,6‐bis benzylidine cyclohexanone analogs of curcumin on gastric adenocarcinoma (AGS) and esophageal squamous cell carcinoma (KYSE30) cancer cells. The results revealed that all synthetic analogs are cytotoxic toward esophageal and gastric cancer cells and more promising than curcumin in cell cycle arrest at G 1 phase and apoptosis induction . Furthermore, these studies recommend that curcumin and related cyclohexanone analogs are effective anticancer agents with various in vitro effects on esophageal cancer cell lines.…”
Section: Introductionmentioning
confidence: 85%
“…Of all the medicinal plants, Curcumin, an important phytochemical of herb Curcuma longa of the ginger family, has been of great interest. In 1870, Curcumin was extracted from Curcuma longa (turmeric plant) for the first time in the crystalline state [42,43]. Multi biofunctionality properties of Curcumin and its derivatives have received enormous attention by the researchers such as antibacterial, antimalarial, antimutagenic, anti-tumor, antioxidant, antiinflammatory activities etc.…”
Section: Combination Of Dabrafenib and Trametinib Which Were Used Asmentioning
confidence: 99%